MANAGEMENT OF COMMERCIAL BANKS AND INDONESIAN SHARIA BANKING - Rico Nur Ilham; Irada Sinta; Frengki Putra Ramansyah; Tahara Alsura; Taufik Hidayat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Commercial bank management in Indonesia is the process of managing banking activities, including planning, organizing, implementing, and supervising bank resources effectively and efficiently, while adhering to prudential principles and applicable regulations. The goal of commercial bank management is to manage all bank operational activities effectively and efficiently. Islamic banking, on the other hand, is a banking system that conducts its business activities based on Islamic sharia principles, as stipulated in Law of the Republic of Indonesia Number 21 of 2008 concerning Islamic Banking. These sharia principles prohibit usury, gharar, maysir, and business activities that conflict with Islamic values. Islamic bank management aims to carry out all operational and strategic processes of the bank while remaining based on Islamic sharia principles, rather than merely seeking financial gain. This study uses a qualitative research method with a literature study approach. ( library research ) . The data collection technique in this study was carried out through documentation studies, namely by collecting, reading, and recording relevant information related to the management of commercial banks and Islamic banking in Indonesia. Overall, the differences in the management of commercial banks and Islamic banks are seen in the profit system, supervision, management orientation, risk management, and managerial objectives. Commercial banks emphasize financial profitability and compliance with conventional regulations, while Islamic banks emphasize sharia compliance, fairness, and socio-economic values. So that Islamic bank management can be said to be more holistic and ethical, while remaining competitive in the national banking system.